Transcriptomic Evidence of Immune Modulation in Subjects With Chronic Trypanosoma cruzi Infection - Ros-Lucas, Albert; Gabaldón-Figueira, Juan Carlos; Martínez-Peinado, Nieves; Losada-Galván, Irene; Posada, Elizabeth; Escabia, Elisa; Martín-Mur, Beatriz; Gut, Marta; Esteve-Codina, Anna; Gascón, Joaquim; Pinazo, María-Jesús; Alonso-Padilla, Julio (The Journal of infectious diseases, 2024)
Abstract Chagas disease is a neglected tropical infection that affects millions of people. This study explores transcriptomic changes in Trypanosoma cruzi-infected subjects before and after treatment. Using total RNA sequencing, gene transcription was analyzed in peripheral blood mononuclear cells from asymptomatic (n = 19) and symptomatic (n = 8) T. cruzi-infected individuals, and noninfected controls (n = 15). Differential expression was compared across groups, and before/after treatment in infected subgroups. Untreated infection showed 12 upregulated and 206 downregulated genes in all T. cruzi-infected subjects, and 47 upregulated and 215 downregulated genes in the symptomatic group. Few differentially expressed genes were found after treatment and between the different infected groups. Gene set enrichment analysis highlighted immune-related pathways activated during infection, with therapy normalizing immune function. Changes in the kynurenine to tryptophan ratio, increased pretreatment, suggested chronic immune fatigue, which was restored posttreatment. These differentially expressed genes offer insights for potential biomarkers and pathways associated with disease progression and treatment response.We performed a transcriptomic analysis on clinical samples from T. cruzi-infected subjects before and after receiving antiparasitic treatment. Significant gene expression changes revealed immune-related pathways activated during infection, normalized by therapy, offering insights for treatment response and biomarkers discovery.